The portable device for continual measurement of radon progenies on filter using the detector Timepix - Bulanek, Boris; Hulka, Jiri; Jilek, Karel; Stekl, Ivan (Radiation protection dosimetry, 2015)
In this article, a portable device was presented for continual measuring of equilibrium equivalent concentration (EEC) of (222)Rn based on the Timepix detector with 300-µm-thick active layer. In order to have a portable device, a filtration head was developed for collecting short-lived radon progenies attached on aerosols. The short-lived progenies are estimated from analysing alphas from decay of (218,214)Po from Millipore filter after termination of filtration. Comparison with beta measurement was done as well. The dependence of EEC on an air flow and filtration time was studied. The low-level detection limit for EEC was estimated from the last 10 min of 3-h decay measurement and was found in the range of 40-70 Bq m(-3). EEC was measured in National Radiation Protection Institute radon chamber, and results were compared with the commercial detector Fritra4.
Keywords: ultrafiltrace; Equipment Design; Air Pollution, Indoor; Radiation Monitoring; Signal Processing, Computer-Assisted; aerosoly; alfa částice; počítačové zpracování signálu; křemík; Analog-Digital Conversion; Silicon; Alpha Particles; Radon Daughters; Ultrafiltration; Beta Particles; beta částice; radon; Radon; analogově digitální konverze; Aerosols; znečištění vzduchu ve vnitřním prostředí; monitorování radiace; radioaktivní látky znečišťující vzduch; dceřiné produkty radonu; design vybavení; Air Pollutants, Radioactive